The Application of Hollow Structured Anodes for Sodium‐Ion Batteries: From Simple to Complex Systems - Xie, Fangxi; Zhang, Lei; Ye, Chao; Jaroniec, Mietek; Qiao, Shi‐Zhang (Advanced materials (Weinheim), 2019)
Hollow structures exhibit fascinating and important properties for energy‐related applications, such as lithium‐ion batteries, supercapacitors, and electrocatalysts. Sodium‐ion batteries, as analogs of lithium‐ion batteries, are considered as promising devices for large‐scale electrical energy storage. Inspired by applications of hollow structures as anodes for lithium‐ion batteries, the application of these structures in sodium‐ion batteries has attracted great attention in recent years. However, due to the difference in lithium and sodium‐ion batteries, there are several issues that need to be addressed toward rational design of hollow structured sodium anodes. Herein, this research news article presents the recent developments in the synthesis of hollow structured anodes for sodium‐ion batteries. The main strategies for rational design of materials for sodium‐ion batteries are presented to provide an overview and perspectives for the future developments of this research area. Hollow‐structured electrode materials exhibit fascinating properties as anodes for sodium‐ion batteries. Recent developments of hollow structured anodes for sodium‐ion batteries are summarized. Additionally, different rational design structures according to the features of sodium‐ion batteries are presented.